Discovery Learning: Pengaruhnya Terhadap Hasil Belajar - Wati, Yulisna; Sartiman, Sartiman (Indonesian Journal of Science and Mathematics Education, 2019)
Abstract: This study aims to  determine wheter there is influence of learning Discovery Learning model to the learning outcomes of class X students in MAN 1 Krui Pesisir Barat. The research that the outhors do is a tipe of research Quasy Experimentals Design, which involves two class groups of experimental class and control class, which the number of students each class of 31 learners. Data collection is obtained by using the test instrument, the test instrument of learning outcomes in the form of multiple choice that is in the form of pretest and postest. Obtained the results of research that there is influence on learning outcomes of learners after using the model of Learning Discovery. T test obtained thitung more than ttabel that is 2,593 more than 2,000 with significant level α = 0,05. So H1 is accepted, indicating that there is influence of Discovery Learning model to the learning result of class X students in MAN 1 Krui Pesisir BaratAbstrak: Penelitian ini bertujuan untuk mengetahui apakah terdapat pengaruh model pembelajaran Discovery Learning terhadap hasil belajar peserta didik kelas X di MAN 1 Krui Pesisir Barat. Penelitian yang penulis lakukan merupakan jenis penelitian Quasi Eksperimen Design, yang melibatkan dua kelompok kelas yaitu kelas eksperimen dan kelas kontrol, dengan jumlah peserta didik pada masing-masing kelas yaitu 31 peserta didik. Pengumpulan data diperoleh dengan menggunakan instrumen tes, instrumen tes hasil belajar berbentuk pilihan ganda yaitu berupa pretest dan postest. Diperoleh hasil penelitian bahwa terdapat pengaruh terhadap hasil belajar peserta didik setelah menggunakan model pembelajaran Discovery Learning. Uji t diperoleh thitung lebih dari ttabel yaitu 2,593 lebih dari  2,000 dengan taraf signifikan α = 0,05. Jadi H1 diterima, yang menandakan bahwa terdapat pengaruh model pembelajaran Discovery Learning terhadap hasil belajar peserta didik kelas X di MAN 1 Krui Pesisir Barat.